PSIV-3 Effect of Protein Source and Soy Hulls Inclusion in Finishing Diets of Feedlot Cattle Fed Free-choice Hay, on Performance and Carcass Characteristics. (7th May 2021) - Pittaluga, Alejandro; Relling, Alejandro E
Abstract: To evaluate the effect of soy-hulls (SH) inclusion in a ground corn-based diet with either distillers dry grains with solubles (DDGS) or soybean meal (SBM) as the protein source (PS), on growth and carcass characteristics of feedlot cattle offered free-access hay; one-hundred and nineteen crossbreed steers (initial BW 566 ± 42kg) were blocked by weight, randomly assigned to 8 pens, and fed for 104 ± 10d. Four dietary treatments were evaluated: 1) DDGS without SH inclusion, 2) DDGS and high inclusion of SH, 3) SBM and low inclusion of SH, and 4) SBM and high inclusion of SH. Diets were formulated to be isonitrogenous. Grass-hay was offered ad-libitum and separate from the concentrates in a different bunk (GrowSafe system). Data was analyzed as a 2×2 factorial considering the fixed effects of treatments and their interaction, and the random effects of block and steer within block. For gain to feed and kidney-pelvic-heart fat (KPH), an interaction occurred (P ≤ 0.10) between PS and SH inclusion (Table 1 and 2, respectively). With greater inclusion of SH, feed efficiencies of steers fed SBM improved compared with feed efficiencies of steers fed DDGS. Steers fed SBM and high SH had the lower KPH content. Feeding SBM increased (P = 0.05) final body weight, tended to increase (P = 0.06) the average daily gain, and decreased (P = 0.05) hay intake compared with steers fed DDGS (Table 1). No differences were observed (P ≥ 0.14) in carcass characteristics between PS and SH inclusion, except for backfat thickness which increased (P = 0.03) with lower SH inclusions (Table 2). These data suggest that opting for SBM as an alternative of DDGS as the protein source of ground corn-based diets, could conceivably enhance the finishing performance of feedlot steers regardless of the SH inclusion levels, and improve feed efficiency with greater levels of dietary SH.